Law Enforcement Against The Circulation Of Illegal Firecrackers In The City Of Medan In Welcoming The Holy Month Of Ramadan - Maswandi Maswandi (International Asia Of Law and Money Laundering, 2023)
The purpose of writing this article is to determine the factors of rampant sales and users of firecrackers in the city of Medan, to find out what efforts are faced by law enforcement against sales and users of firecrackers in the city of Medan and to find out what obstacles faced by law enforcement against sales and users of firecrackers in the city of Medan, especially in the holy month of ranadhan. The Data required in this paper are primary and secondary data. Primary Data obtained by conducting field research by interviewing respondents and informants. While secondary data obtained through literature research conducted by studying textbooks, legislation, and opinions parasarjana. Conclusion it is known that the factors undertaken by the police to be important in preventing the circulation of illegal firecrackers in the community, lack of public awareness of the law and the dangers posed by the use of illegal firecrackers, preventive countermeasures are carried out before the violation occurs by preventing the violation does not occur, barriers to the lack of information received, Lack of budget funds received by the National Police in carrying out patrol functions to cope with the circulation of firecrackers. It is recommended to all relevant parties to always provide counseling and socialization of the dangers of firecrackers to the community, so that Banda Aceh is safe from the circulation of firecrackers, because firecrackers are very disturbing to the comfort of the community,as parents it is very important to prohibit playing firecrackers, at least parents supervise children when playing firecrackers in the environment.